Bio-Ethanol Production from Textile Cotton Waste via Dilute Acid Hydrolysis and Fermentation by Saccharomyces cerevisiae - Kavita Sharma3; Sushma Dubey4, B. Chandrashekhar1*, Mohit S. Mishra2, (Journal of Ecobiotechnology, 2011)
The present work deals with the process bioconversion of cellulose from textile cotton waste, obtained from a textile industry, into ethanol by using the methods of acid pretreatment, hydrolysis and fermentation by Saccharomyces cerevisiae. The process includes the pretreatment method of the cotton waste fibers with dilute sulphuric acid and heating the mixture at a high temperature to break the crystalline structure of the cellulose to facilitate the hydrolysis of cellulosic component by dilute acids. The hydrolysis of the cellulose content into sugars is done by dilute acid hydrolysis that involves incubation period at a high temperature for 72 hours. Finally, the fermentation of the hydrolyzed waste is done using Saccharomyces cerevisiae under proper incubation conditions to produce ethanol.